Rethinking the role of fat oxidation: substrate utilisation during high-intensity interval training in well-trained and recreationally trained runners - Hetlelid, Ken J (BMJ Open Sport Exerc Med, 2015)
BACKGROUND: Although carbohydrate is the predominant fuel source supporting high-intensity exercise workloads, the role of fat oxidation, and the degree to which it may be altered by training status, is less certain. METHODS: We compared substrate oxidation rates, using indirect calorimetry, during a high-intensity interval training (HIT) session in well-trained (WT) and recreationally trained (RT) runners. Following preliminary testing, 9 WT (VO(2max) 71±5 mL/min/kg) and 9 RT (VO(2max) 55±5 mL/min/kg) male runners performed a self-paced HIT sequence consisting of six, 4 min work bouts separated by 2 min recovery periods on a motorised treadmill set at a 5% gradient. RESULTS: WT and RT runners performed the HIT session with the same perceived effort (rating of perceived exertion (RPE) =18.3±0.7 vs 18.2±1.1, respectively), blood lactate (6.4±2.1 vs 6.2±2.5 mmol/L) and estimated carbohydrate oxidation rates (4.2±0.29 vs 4.4±0.45 g/min; effect size (ES) 90% confidence limits (CL)=−0.19±0.85). Fat oxidation (0.64±0.13 vs 0.22±0.16 g/min for WT and RT, respectively) accounted for 33±6% of the total energy expenditure in WT vs 16±6% in RT most likely very large difference in fat oxidation (ES 90% CL=1.74±0.83) runners. Higher rates of fat oxidation had a very large correlation with VO(2max) (r=0.86; 90% CI (0.7 to 0.94). CONCLUSIONS: Despite similar RPE, blood lactate and carbohydrate oxidation rates, the better performance by the WT group was explained by their nearly threefold higher rates of fat oxidation at high intensity.